1996
DOI: 10.1002/(sici)1096-9861(19960219)365:4<585::aid-cne6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Axonal projection patterns of neurons in the secondary gustatory nucleus of channel catfish

Abstract: The second gustatory nucleus of teleost fishes receives ascending fibers from the primary gustatory center in the medulla and sends efferent fibers to several nuclei in the inferior lobe of the diencephalon. Similar to the corresponding parabrachial nucleus in birds and mammals, the secondary gustatory nucleus of catfish consists of several cytoarchitectonically distinct subnuclei which receive input from different portions of the primary gustatory nuclei. However, it is unclear how the subnuclear organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Morphologically speaking, the gustatory system has been extensively studied (reviewed in Hara, 1994;Kasumyan and Døving, 2003;Hansen and Reutter, 2004) and will only be briefly mentioned here. Many classical studies have described the morphology and distribution of fish taste buds (e.g., Crisp et al, 1975;Grover-Johnson and Farbman, 1976;Ezeasor, 1982;Marui et al, 1983;_ Zuwata and Jakubowski, 1993;Fishelson et al, 2004), their innervation and central organization of the gustatory system (e.g., Kotrschal and Finger, 1996;Lamb and Finger, 1996;Yoshimoto et al, 1998;Folgueira et al, 2003), and found these to be quite similar to mammals. Fish are characterized by having more taste buds than any other animal, which can have both an external (extraoral) and internal (oral) location.…”
Section: The Gustatory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphologically speaking, the gustatory system has been extensively studied (reviewed in Hara, 1994;Kasumyan and Døving, 2003;Hansen and Reutter, 2004) and will only be briefly mentioned here. Many classical studies have described the morphology and distribution of fish taste buds (e.g., Crisp et al, 1975;Grover-Johnson and Farbman, 1976;Ezeasor, 1982;Marui et al, 1983;_ Zuwata and Jakubowski, 1993;Fishelson et al, 2004), their innervation and central organization of the gustatory system (e.g., Kotrschal and Finger, 1996;Lamb and Finger, 1996;Yoshimoto et al, 1998;Folgueira et al, 2003), and found these to be quite similar to mammals. Fish are characterized by having more taste buds than any other animal, which can have both an external (extraoral) and internal (oral) location.…”
Section: The Gustatory Systemmentioning
confidence: 99%
“…Three cranial nerves are responsible for relaying gustatory information directly to the central nervous system: (1) the facial (VII) nerve, projecting into taste buds on the extraoral surface (lips, barbels, fins, and body surface) and mandibular arch, including oral taste buds of rostral palate; (2) glossopharyngeal (IX) nerve innervating the pharyngeal arches and posterior part of the oral cavity; and (3) vagus (X) nerve that projects into the branchial arches and pharynx (Hara, 1994;Kasumyan and Døving, 2003;Yasuoka and Abe, 2009). These nerves relay information to the primary gustatory centers in the medulla-facial, glossopharyngeal, and vagal lobes, respectively-and from here efferent fibers connect to the secondary gustatory nucleus, which finally project to several nuclei (or tertiary gustatory centers) in the inferior lobe of the diencephalon (Kotrschal and Finger, 1996;Lamb and Finger, 1996;Yoshimoto et al, 1998;Folgueira et al, 2003).…”
Section: The Gustatory Systemmentioning
confidence: 99%
“…These traits might be related to the neuroendocrine controls exerted by the hypothalamus. However, several nuclei of the hypothalamus and preoptic region serve as tertiary gustatory centres (Folgueira et al, 2003;Lamb and Finger, 1996), and the increase in these nuclei might correspond to the increase in taste bud number in cavefish (Jeffery et al, 2000). Further investigations are clearly needed to functionally interpret this hypothalamic difference between cavefish and surface fish.…”
Section: Shh and Cell Proliferation: A Bigger Hypothalamus In Cavefishmentioning
confidence: 99%
“…Fiber connections of the SGN have been studied in several species of teleosts. The SGN projects to diencephalic tertiary gustatory centers, mainly to the preglomerular tertiary gustatory nucleus (pTGN or its presumed homologue) and inferior lobe (crucian carp: Morita et al,1980, 1983; ictalurid catfishes: Kanwal et al,1988; channel catfish: Lamb and Finger,1996; green sunfish: Wullimann,1988; Nile tilapia: Yoshimoto et al,1998; filefish: Shimizu et al,1999; red cichlid: Ahrens and Wullimann,2002). Ascending connections from the diencephalic gustatory structures to the telencephalon have been reported only in a few species of teleosts: ictalurid catfishes (Kanwal et al,1988; Lamb and Caprio,1993), Nile tilapia (Yoshimoto et al,1998), and rainbow trout (Folgueira et al,2003).…”
mentioning
confidence: 99%